Cationic urethane resin composition

The cationic urethane resin composition, characterized by a specific structural unit, addresses the challenges of durability and stability in polyurethane coatings, achieving enhanced performance in both durability and water dispersibility.

JP7658448B2Active Publication Date: 2025-04-08DIC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023547254
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-08
Publication Date
2025-04-08
Estimated Expiration
2041-06-08

AI Technical Summary

Technical Problem

Existing cationic urethane resin compositions struggle to achieve excellent durability and stability in polyurethane coatings, particularly in terms of long-term storage and water dispersibility.

Method used

A cationic urethane resin composition is developed, featuring a cationic urethane resin with a specific structural unit represented by formula (1), which includes an alkyl group and a quaternizing agent residue, enhancing the resin's durability and water dispersibility.

Benefits of technology

The composition provides a polyurethane coating with significantly improved durability, extension stress, and heat-resistant discoloration resistance, while maintaining excellent water dispersibility and long-term storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658448000001
    Figure 0007658448000001
  • Figure 0007658448000002
    Figure 0007658448000002
  • Figure 0007658448000003
    Figure 0007658448000003
Patent Text Reader

Abstract

The present invention provides a cationic urethane resin composition containing a cationic urethane resin (A) and water (B), characterized in that the cationic urethane resin (A) has a specific structural unit. The cationic urethane resin composition of the present invention can provide a polyurethane film having excellent durability. The cationic urethane resin composition of the present invention also has excellent dispersibility in water and stability during long-term storage. Therefore, the cationic urethane resin composition of the present invention can be particularly suitably used for the production of building materials and steel plates for home appliances, plastic films and plastic molded products, receiving agents for recording materials for inkjet printing, and bundling agents for glass fibers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cationic urethane resin composition. [Background technology]

[0002] Urethane resin compositions in which a urethane resin is dispersed in water can reduce the burden on the environment compared to conventional organic solvent-based urethane resin compositions, and therefore have recently begun to be suitably used as materials for producing synthetic leather, gloves, and coating agents for curtains, sheets, and the like (see, for example, Patent Document 1).

[0003] The required properties of the urethane resin composition include, of course, excellent dispersibility in water and stability during long-term storage, as well as further improvement in the durability of the polyurethane film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP2016-222921A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a cationic urethane resin composition which produces a polyurethane film having excellent durability. [Means for solving the problem]

[0006] The present invention provides a cationic urethane resin composition containing a cationic urethane resin (A) and water (B), wherein the cationic urethane resin (A) has a structural unit represented by the following formula (1):

[0007] [ka] (In formula (1), R 1 represents a structure represented by the following formula (2) or formula (3), and R 2 and R 3 each independently represents an alkyl group which may contain an alicyclic structure, R 4 represents a hydrogen atom or a residue of a quaternizing agent introduced by a quaternization reaction, and X - indicates an anionic counter ion.)

[0008] [ka] In formula (2), the two benzene rings and the oxygen atom are each independently linked at the 2-position, 3-position, 4-position, 5-position, or 6-position of the benzene ring; R 1 and R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a benzene ring.

[0009] [ka] (In formula (3), the two substituents linked to the cycloring are at the ortho position. ,again is in para position.) Effect of the Invention

[0010] The cationic urethane resin composition of the present invention can provide a polyurethane film having excellent durability. In addition, the cationic urethane resin composition of the present invention has excellent dispersibility in water and stability during long-term storage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The cationic urethane resin composition of the present invention contains a cationic urethane resin (A) having a specific structural unit, and water (B).

[0012] In order to obtain excellent durability, it is essential that the cationic urethane (A) has a structural unit represented by the following formula (1).

[0013] [ka] (In formula (1), R 1 represents a structure represented by the following formula (2) or formula (3), and R 2 and R 3 each independently represents an alkyl group which may contain an alicyclic structure, R 4 represents a hydrogen atom or a residue of a quaternizing agent introduced by a quaternization reaction, and X - indicates an anionic counter ion.)

[0014] [ka] In formula (2), the two benzene rings and the oxygen atom are each independently linked at the 2-position, 3-position, 4-position, 5-position, or 6-position of the benzene ring; R 1 and R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a benzene ring.

[0015] [ka] (In formula (3), the two substituents linked to the cycloring are at the ortho position. ,again is in para position.)

[0016] In the formula (1), R 2 and R 3 Each of X independently represents an alkyl group which may contain an alicyclic structure, and is preferably a propyl group, a butyl group, or a pentyl group, and more preferably a butyl group. The residue of the quaternizing agent is preferably a methyl group or an ethyl group. - is preferably an anionic ion formed when acetic acid, phosphoric acid, dibutyl acid, benzyl chloride, or the like is used as an acid or quaternizing agent described below.

[0017] The cationic urethane resin (A) can improve the tensile stress of the polyurethane film in particular, and can also improve the heat resistance, by using the epoxy raw material having the hard chemical structure.

[0018] The cationic urethane resin (A) can be, for example, a reaction product of a polyol (a1) containing an amino group-containing polyol (a1-1), which is a reaction product of a diglycidyl ether (s1) having a structure represented by the formula (2) or (3) and a secondary amine (s2), and a polyisocyanate (a2).

[0019] As the diglycidyl ether having the structure represented by the formula (2), for example, bisphenol A diglycidyl ether, bisphenol AP diglycidyl ether, bisphenol B diglycidyl ether, bisphenol BP diglycidyl ether, bisphenol E diglycidyl ether, bisphenol F diglycidyl ether, bisphenol C diglycidyl ether, etc. can be used. These compounds may be used alone or in combination of two or more. Among these, bisphenol F diglycidyl ether is preferred because it provides even better durability.

[0020] As the diglycidyl ether having the structure represented by the formula (3), for example, a compound represented by the following formula (3-1) or a compound represented by the following formula (3-2) can be used. These compounds may be used alone or in combination of two or more. Among these, the compound represented by the following formula (3-1) is preferred in terms of obtaining even more excellent durability.

[0021] [ka]

[0022] [ka]

[0023] As the secondary amine (s2), for example, dimethylamine, diethylamine, di-n-propylamine, diisopropylamine, di-n-pentylamine, di-tert-butylamine, di-sec-butylamine, di-n-butylamine, di-n-pentylamine, di-n-heptylamine, di-n-octylamine, diisooctylamine, dinonylamine, diisononylamine, di-n-decylamine, di-n-undecylamine, di-n-dodecylamine, di-n-pentadecylamine, di-n-octadecylamine, di-n-nonadecylamine, di-n-eicosylamine, etc. can be used. These compounds may be used alone or in combination of two or more. Among these, aliphatic amines having 2 to 18 carbon atoms are preferred, and aliphatic amines having 3 to 8 carbon atoms are more preferred, in view of obtaining even more excellent durability and water dispersion stability.

[0024] The method for producing the amino group-containing polyol (a1-1) may be, for example, to mix the diglycidyl ether (s1) and the secondary amine (s2) in such an amount that 1 equivalent of NH group is mixed with 1 equivalent of epoxy group, and to carry out a ring-opening addition reaction without a catalyst at room temperature or under heating. The reaction may be carried out in an organic solvent as necessary, and may be carried out, for example, at a temperature in the range of 60 to 120°C for 30 minutes to 14 hours.

[0025] Examples of the organic solvent that can be used include ketone solvents such as acetone, diethyl ketone, methyl ethyl ketone, and methyl isobutyl ketone; ether solvents such as diethyl ether and ethylene glycol dimethyl ether; acetate ester solvents such as ethyl acetate and butyl acetate; hydrocarbon solvents such as benzene, hexane, toluene, and xylene; and amide solvents such as dimethylformamide. These organic solvents may be used alone or in combination of two or more.

[0026] The amount of the amino group-containing polyol (a1-1) used is preferably in the range of 0.1 to 30 mass %, more preferably 1 to 15 mass %, based on the total mass of the cationic urethane resin (A), in terms of obtaining even better durability.

[0027] The polyol (a1) contains the amino group-containing polyol (a1-1) as an essential component, but may contain other polyols as necessary. The content of the amino group-containing polyol (a1-1) in the polyol (a1) is preferably in the range of 0.2 to 50% by mass, more preferably in the range of 0.5 to 30% by mass, in order to obtain even more excellent durability.

[0028] As the other polyol, for example, polycarbonate polyol, polyester polyol, polyether polyol, etc. can be used. These polyols may be used alone or in combination of two or more. Among these, polycarbonate polyol is preferred because it provides even better weather resistance.

[0029] The number average molecular weight of the other polyol is preferably in the range of 500 to 10,000, more preferably in the range of 700 to 5,000, in terms of obtaining even better durability. The number average molecular weight of the other polyol is a value measured by gel permeation chromatography (GPC).

[0030] In order to obtain even better aqueous dispersion stability, it is preferable that the tertiary amino groups of the amino group-containing polyol (a1-1) are partly or entirely neutralized with an acid or quaternized with a quaternizing agent.

[0031] Examples of the acid that can be used include organic acids such as formic acid, acetic acid, propionic acid, succinic acid, glutaric acid, butyric acid, lactic acid, malic acid, citric acid, tartaric acid, malonic acid, and adipic acid; organic sulfonic acids such as sulfonic acid, paratoluenesulfonic acid, and methanesulfonic acid; and inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, phosphorous acid, and hydrofluoric acid. These acids may be used alone or in combination of two or more.

[0032] Examples of the quaternizing agent include dialkyl sulfates such as dimethyl sulfuric acid and diethyl sulfate, halogenated alkyl compounds such as methyl chloride, ethyl chloride, benzyl chloride, methyl bromide, ethyl bromide, benzyl bromide, methyl iodide, ethyl iodide, and benzyl iodide, methyl sulfonate compounds such as methyl methanesulfonate, methyl paratoluenesulfonate, and methyl methanesulfonate, and epoxy compounds such as ethylene oxide, propylene oxide, styrene oxide, epichlorohydrin, allyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether. These compounds may be used alone or in combination of two or more.

[0033] The amount of the acid or quaternizing agent used is, for example, within the range of 0.1 to 3 equivalents per equivalent of the tertiary amino group in the amino group-containing polyol (a1-1).

[0034] Examples of the polyisocyanate (a2) that can be used include aliphatic polyisocyanates such as hexamethylene diisocyanate and lysine diisocyanate; alicyclic polyisocyanates such as cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate and norbornene diisocyanate; and aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimidized diphenylmethane polyisocyanate. These polyisocyanates may be used alone or in combination of two or more.

[0035] The amount of the polyisocyanate (a2) used is preferably in the range of 5 to 60 mass %, more preferably 10 to 45 mass %, based on the total mass of the cationic urethane resin (A), in terms of obtaining even better durability.

[0036] Examples of the method for producing the cationic urethane resin (A) include a method in which the amino group-containing polyol (a1-1), other polyol, and the polyisocyanate (a2) are all charged in a vessel and reacted in an organic solvent or in the absence of a solvent to obtain a polyurethane resin, and further a part or all of the tertiary amino groups in the polyurethane resin are neutralized with an acid and / or quaternized with the quaternizing agent, and then water (B) is added to disperse the resulting polyurethane resin.

[0037] The weight average molecular weight of the cationic urethane resin (A) is preferably in the range of 4,000 to 300,000, and more preferably in the range of 7,000 to 200,000, in order to obtain even better durability and water dispersion stability. The weight average molecular weight of the cationic urethane resin (A) is a value measured by gel permeation chromatography (GPC).

[0038] As the water (B), for example, ion-exchanged water, distilled water, etc. can be used. These waters may be used alone or in combination of two or more. The content of the water (B) is, for example, in the range of 35 to 90 mass %.

[0039] The cationic urethane resin composition of the present invention contains the cationic urethane resin (A) and the water (B), and may contain other additives, if necessary.

[0040] Examples of the other additives that can be used include neutralizing agents, emulsifiers, crosslinking agents, thickeners, urethane catalysts, fillers, foaming agents, pigments, dyes, oil repellents, hollow foams, flame retardants, defoamers, leveling agents, antiblocking agents, etc. These additives may be used alone or in combination of two or more.

[0041] As described above, the cationic urethane resin composition of the present invention can provide a polyurethane film having excellent durability. In addition, the cationic urethane resin composition of the present invention has excellent dispersibility in water and stability during long-term storage. Therefore, the cationic urethane resin composition of the present invention can be particularly suitably used for the manufacture of building materials and steel plates for home appliances, plastic films and plastic molded products, receiving agents for recording materials for inkjet printing, and bundling agents for glass fibers. EXAMPLES

[0042] The present invention will now be described in more detail with reference to examples.

[0043] [Synthesis Example 1] Synthesis of amino group-containing polyol (a1-1-1) A four-neck flask equipped with a stirrer, a reflux condenser, a thermometer, and a dropping device was charged with 56 parts by mass of bisphenol F type diglycidyl ether, and then the flask was replaced with nitrogen. Next, the flask was heated until the temperature inside reached 70°C, and then 44 parts by mass of di-n-butylamine was dropped into the flask using the dropping device for 30 minutes. After completion of the reaction, the mixture was reacted at 90°C for 10 hours to obtain an amino group-containing polyol (a1-1-1).

[0044] [Synthesis Example 2] Synthesis of amino group-containing polyol (a1-1-2) An amino group-containing polyol (a1-1-2) was obtained in the same manner as in Synthesis Example 1, except that 56 parts by mass of the compound represented by the formula (3-1) was used instead of 56 parts by mass of bisphenol F diglycidyl ether.

[0045] [Comparative Synthesis Example 1] Synthesis of amino group-containing polyol (aR1) A four-neck flask equipped with a stirrer, a reflux condenser, a thermometer, and a dropping device was charged with 590 parts by mass of polypropylene glycol diglycidyl ether (epoxy equivalent: 201 g / equivalent), and the atmosphere in the flask was replaced with nitrogen. Next, the flask was heated until the temperature inside reached 70°C, and then 380 parts by mass of di-n-butylamine was dropped into the flask using the dropping device for 30 minutes. After completion of the reaction, the mixture was reacted at 90°C for 10 hours to obtain an amino group-containing polyol (aR1).

[0046] [Example 1] Into a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 30.6 parts by mass of polycarbonate polyol ("Nippolan 980R" manufactured by Nippon Polyurethane Industry Co., Ltd.) and 18.7 parts by mass of MEK were added and stirred while cooling to 50° C. After stirring, 8.7 parts by mass of 4,4'-dicyclohexylmethane diisocyanate and 0.01 parts by mass of stannous octoate were added and reacted at 70° C. for 2 hours. Thereafter, 3.1 parts by mass of the amino group-containing polyol (a1-1-1) obtained in Synthesis Example 1 was added and reacted for 4 hours, followed by adding 0.85 parts by mass of aminoethylethanolamine and carrying out a chain extension reaction for 1 hour. Next, 10.6 parts by mass of MEK and 0.75 parts by mass of acetic acid were added, and the mixture was kept at 55° C. for 1 hour, then cooled to 40° C., and 85 parts by mass of ion-exchanged water was added to prepare an aqueous dispersion, which was distilled under reduced pressure to obtain a cationic urethane resin composition (1) with a non-volatile content of 35% by mass.

[0047] [Example 2] A cationic urethane resin composition (2) was obtained in the same manner as in Example 1, except that 3.1 parts by mass of the amino group-containing polyol (a1-1-1) obtained in Synthesis Example 1 was changed to 3.2 parts by mass of the amino group-containing polyol (a1-1-2) obtained in Synthesis Example 2.

[0048] [Comparative Example 1] A cationic urethane resin composition (R1) was obtained in the same manner as in Example 1, except that 3.1 parts by mass of the amino group-containing polyol (a1-1-) obtained in Synthesis Example 1 was changed to 3.5 parts by mass of the amino group-containing polyol (aR1) obtained in Comparative Synthesis Example 1.

[0049] [Method of measuring number average molecular weight and weight average molecular weight] The number average molecular weight of the polyol and the weight average molecular weight of the cationic urethane resin are values ​​measured by gel permeation column chromatography (GPC) under the following conditions.

[0050] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 0.4% by mass in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following standard polystyrene.

[0051] (Standard polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0052] [Durability evaluation method] (1) Evaluation of tensile stress The cationic urethane resin composition obtained in the examples and comparative examples was coated on a release paper so that the film thickness after drying was 150 μm, and after drying for one day at 23° C. and 65% humidity, the polyurethane film was dried at 150° C. for 5 minutes. The specimen was peeled off from the release paper and cut to a width of 5 mm to prepare a test piece. The test piece was stretched at 300 mm / min using a Tensilon universal material testing machine manufactured by A&D Co., Ltd., and the elongation stress (MPa) was measured at 100%, 200%, and 300% tension. The higher the elongation stress, the better the durability.

[0053] (2) Evaluation of heat discoloration resistance The cationic urethane resin compositions obtained in the Examples and Comparative Examples were coated on release paper so that the film thickness after drying was 150 μm, and then dried for one day at 23° C. and 65% humidity, followed by drying for 5 minutes at 150° C. to obtain a polyurethane film. The test piece peeled from the release paper was heated at 200° C. for one hour, and the color difference ΔE before and after heating was measured using a “CM-5” manufactured by Konica Minolta, Inc. The lower the ΔE value, the better the durability.

[0054] [Table 1]

[0055] As shown in Examples 1 and 2, it was found that the cationic urethane resin composition of the present invention was able to give a polyurethane film having excellent durability.

[0056] On the other hand, Comparative Example 1 is an embodiment in which a cationic urethane resin composition other than those specified in the present invention was used, and durability was insufficient.

Claims

1. A cationic urethane resin composition comprising a cationic urethane resin (A) and water (B), The cationic urethane resin (A) has a structural unit represented by the following formula (1): the cationic urethane resin (A) is a reaction product of a polyol (a1) including an amino group-containing polyol (a1-1) which is a reaction product of a diglycidyl ether (s1) and a secondary amine (s2), and a polyisocyanate (a2); The cationic urethane resin composition, characterized in that the diglycidyl ether (s1) contains bisphenol F diglycidyl ether, a compound represented by the following formula (3-1), or a compound represented by the following formula (3-2): 【Chemistry 1】 (In formula (1), R 1 represents a structure represented by the following formula (2) or formula (3), R 2 and R 3 each independently represents an alkyl group which may contain an alicyclic structure, R 4 represents a hydrogen atom or a residue of a quaternizing agent introduced by a quaternization reaction, and X - indicates an anionic counter ion.) 【Chemistry 2】 In formula (2), the two benzene rings and the oxygen atom are each independently linked at the 2-position, 3-position, 4-position, 5-position, or 6-position of the benzene ring; R 1 and R 2 indicates a hydrogen atom.) 【Chemistry 3】 In formula (3), the two substituents linked to the cyclo ring are located at the ortho or para positions. 【Chemistry 4】 【Chemistry 5】

2. The cationic urethane resin composition according to claim 1, wherein the amount of the amino group-containing polyol (a1-1) used is in the range of 0.1 to 30 mass% of the total mass of the raw materials for the cationic urethane resin (A).

3. 2. The cationic urethane resin composition according to claim 1, wherein the polyol (a1) further contains a polycarbonate polyol.

Citation Information

Patent Citations

  • UV cured cathode electrophoresis paint with side chain containing ammonium salt positive ions and preparation method therefor

    CN105176155A

  • denchakutosoyososeibutsuoyobidenchakutosohoho

    JP1976103135A

  • Composition for cationic electrodeposition primer

    JP1984011378A

  • Production of flame retardant epoxy resin, flame retardant epoxy resin composition and matrix resin composition for printed circuit board

    JP1996291212A

  • Inkjet receiving agent and inkjet recording medium using it

    JP2006150931A